PENGEMBANGAN MODUL BERBASIS MATEMATIKA REALISTIK BERCIRIKAN BUDAYA INDONESIA - Agung Deddiliawan Ismail; Anis Farida Jamil (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
One of the negative effects of globalization is the reduced love for culture in the younger generation. Increasing the love of culture in the younger generation can be done in mathematics learning. Realistic mathematics connects mathematics learning with daily life activities. Realistic mathematics characterized by Indonesian culture is contained in modules with the aim of learning mathematics and also can increase students' knowledge about Indonesian culture. This study aims to develop modul based on realistic mathematical characterized by Indonesian culture that is valid and practical. The instruments used in this study were validation sheets and student response questionnaire sheets. Validation sheet to obtain module validity data while student response questionnaire sheets are used to obtain module practicality data. The method used in this study is through three stages, namely the stage of defining, designing, and developing. This research and development produces modul based on realistic mathematical characterized by Indonesian culture that is valid and practical. Valid is obtained from the data analysis sheet validation filled by expert validators. The practicality of the module was obtained from the results of the student response questionnaire which showed a positive response.